"It's a blessing and a curse": Perspectives on tablet use in children with autism spectrum disorder. (January 2017) - King, Amie M; Brady, Kathryn W; Voreis, Grayce
Background and aims: This qualitative study was conducted to obtain information regarding education professionals' (i.e., classroom teachers' and speech-language pathologists') perspectives about tablet technology use in classrooms of children with Autism Spectrum Disorder (CWASD). Methods: Seventeen education professionals from a special day school for CWASD participated in one of four focus groups that provided information and insight regarding the context in which tablets are being used, challenges in implementing tablets, and perspectives on how tablets can be used most effectively. Results: Four interrelated themes emerged from the data including the participants' perspectives related to: (a) the distinct uses of tablets; (b) challenges and challenging behavior associated with tablet use; (c) causal factors of the challenges; and (d) the value of tablets, and the continued desire and dedication to using the tablets; Conclusions and implications: The results from this study suggest that education professionals have unique and insightful opinions related to tablets. There appears to be gaps between the current research base on tablet use in CWASD and "real world" practice, suggesting that further research is needed in the implementation of tablets in classrooms of CWASD.